2006
DOI: 10.1002/ajp.20287
|View full text |Cite
|
Sign up to set email alerts
|

Histology of the sternal and suprapubic skin areas in lion tamarins (Leontopithecus sp. Callitrichidae–Primates)

Abstract: Though knowledge regarding the biology and morphology of lion tamarins is scarce in the literature, it is very important for their conservation. This paper focuses on the anatomical and histological aspects of the glands involved in the scent-marking behavior of lion tamarins. It examines the histological aspects of sternal and suprapubic skin sections of specimens that were preserved in formaldehyde and were the property of the Rio de Janeiro Primatology Center Museum. Eighteen specimens from three lion tamar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Our study groups varied in composition of their scent-gland (Fontani et al, 2014) and the suprapubic and sternal scent-gland skin of lion tamarins, Leonthopithecus sp. (Moraes et al, 2006), showed no difference between the tissues of these different glands. The same can, therefore, be expected for the two tamarin species studied here.…”
Section: Compounds Detected In Tamarin Scent-gland Secretionsmentioning
confidence: 84%
“…Our study groups varied in composition of their scent-gland (Fontani et al, 2014) and the suprapubic and sternal scent-gland skin of lion tamarins, Leonthopithecus sp. (Moraes et al, 2006), showed no difference between the tissues of these different glands. The same can, therefore, be expected for the two tamarin species studied here.…”
Section: Compounds Detected In Tamarin Scent-gland Secretionsmentioning
confidence: 84%
“…Noticeably, images depicting patterns of progressive, polarized holocriny in sebaceous acini are more informative than features collected from museum specimens. Skin samples collected from these animals [Moraes et al, 2006], but results provide a sharp differential step characterization of the holocrine process that is marked by an apoptotic feature gradient of lipogenic degeneration. Moreover, the present data further our understanding of scent glands in male tamarins.…”
Section: Discussionmentioning
confidence: 99%
“…The aims of this study, employing light microscopy, are: (1) to provide an alternative approach to the traditional use of animals from museum collections (that have undergone a prolonged in toto fixation with formic aldehyde [Moraes et al, 2006]) by investigating specimens frozen immediately after natural death; (2) to further the understanding of male glands that, to date, have been largely neglected.…”
Section: Introductionmentioning
confidence: 99%
“…In black lion tamarins, fur‐rubbing on the cabreúva trees stood out from territory marking, a swift behavior related to inter‐ and intragroup social communication and commonly displayed by tamarins (Heymann, 2006). Indeed, callitrichids possess epithelial glands in their sternal and anogenital regions that produce specific odors (Miller et al, 2003; Moraes et al, 2006). Individuals rub these specific areas against horizontal or inclined substrates to deposit their olfactive signature (Heymann, 2006).…”
Section: Figurementioning
confidence: 99%
“…In black lion tamarins, fur-rubbing on the cabreúva trees stood out from territory marking, a swift behavior related to inter-and intragroup social communication and commonly displayed by tamarins (Heymann, 2006). Indeed, callitrichids possess epithelial glands in their sternal and anogenital regions that produce specific odors (Miller et al, 2003;Moraes et al, 2006). Individuals rub these specific areas against horizontal or inclined substrates to deposit their F I G U R E 1 Percentage of videos captured at the cabreúva trees (Myroxylon peruiferum) per species, recorded by camera trap footage in three different field sites: a fragment in the municipality of Guareí (127 videos), the Morro do Diabo State Park (MDSP; 440 videos), and the Santa Maria (SMA) fragment (34 videos).…”
mentioning
confidence: 99%